OBESITY RELATIONSHIP, METABOLIC SYNDROME AND INSULIN RESISTANCE: A SYSTEMATIC REVIEW - Vitor Cavalcante Alves, João (Health and Society, 2024)
Objective: The present study aims to describe the relationship of obesity with metabolic syndrome and insulin resistance in obese patients. Methodology: The present study is a bibliographic review that seeks to study articles on the biochemistry of obesity and insulin resistance. 18,955 PUBMED databases and Virtual Health Library of the Ministry of Health were consulted with the following filters: randomized study articles and epidemiological review articles. Articles written in English published between 2006 and 2023 were used in the research. The research was conducted in 2 phases: articles and summaries screening phase that were used in the bibliographic review where 7 articles were selected, then the work were read and built the Scientific article. RESULTS: Longitudinal research of literature review points out that obesity develops an inflammatory process of dysfunctional adipocytes where cytokines ampha and macrophages are triggered causing an accumulation of systemic fatty acids in the body’s tissues such as: liver and muscle pancreas generating lipotoxicity and one one Systemic inflammation that prevents adequate insulin signaling. Metabolic syndrome was diagnosed in 45.5% of obese patients and insulin resistance at 29.1%. Insulin resistance had an association with HDL-cholesterol (p = 0.032) and with metabolic syndrome (p = 0.006). The body composition indicators were correlated with insulin resistance (p